A feasibility study on Toy Library - Felizardo, Francesca Louise N.; Franco, Lizabeth Ann D.; Mendoza, Felize Angela O.; Yabut, Camille Joy A. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
One important contributor to a child's development and growth is his play experience for this hones him physically, mentally and socially. Nowadays, the most common mean of play is through the usage of toys. Toys are classified as either traditional toys or electronic gadgets. Traditional toys are toys without a video game component while electronic gadgets are toys needing a video game component. Even in this technological age, wherein a rapid growth in the demand for electronic gadgets is evident, there is still a relatively steady demand for traditional toys and games observed. In addition, traditional toys and games still comprise a larger percentage of overall sales. This information together with the realization that traditional toys and games better promote learning through interaction compared to electronic gadgets, paved way for the concept of The Toy Library. The Toy Library is a service type of business which offers sit down play, toy loaning and learning sessions for children ages 4-12 years old. With this type of services, the library will be able to tap a middle class type of market, specifically double income families. To reach its target market, the service is placed in an area close to private elementary schools in the largest school district of Quezon City. the service will invest in a variety of promotional and marketing activities to tap its target market for this type of a business concept is relatively new to Filipinos. Existing toy libraries in the Philippines are usually used for outreach and consequently are not for profit. Besides existing toy libraries, other competitors of the service include child day care centers and play centers which are more widely known compared to the toy library. Although this is the case, the library has its competitive advantage of the Toy Library is its toy loaning service since it is the only one among its competitors that offers the service. The result of this market study is essential in determining the library's capacity, processes, policies, operations and their incurred costs. These are discussed in detail in this paper. Given the costs computed, it is most suitable for the service to run as a corporation. It is then defined in the Technical Study the specific services offered by the business, its operating procedures, pricing scheme and policies. Based on the results of the Market Study, the specific location where the Toy Library will be placed was determined in such a way that the Toy Library will be accessible to its target market. This was done using the Center of Gravity Method. Material, equipment and furniture requirements and the corresponding cost have been determined. With this, the design and layout of the facility was created. To facilitate the operation of the business, manpower requirements were identified and the costs associated to the hiring of employees were computed. Inflation was considered in computing for the costs regarding the operation of the Toy Library facility can also be found in the Technical Study. The results of the Technical Study were then used in evaluating the financial feasibility of the business. In evaluating the financial feasibility of the Toy Library business, the amount of investment needed to put the business up was determined. Different sources of financing were evaluated and the most suitable option for the business was chosen. Pro forma statement, such as income statements, balance sheets and cash flow statements for five years were created. Certain ratios were computed in order to determine the company's profitability and capability to pay off its liabilities. The ratios show that the company will continue to grow more profitable beginning the second year of operation. The economic benefits of the Toy Library service were determined. Also, the business' contribution to National Objective was analyzed, together with the benefits that the business can provide to other involved entities. These were studied in order to determine if the Toy Library Service is socially feasible. The results of the completion of the market, technical, financial, and social profitability studies will determine if the Toy Library Service is indeed feasible.
Submitted in partial fulfillment of the course requirements in IE 153 : Project development and management.
Keywords: Toy lending libraries -- Philippines; Feasibility studies